The Role of Community in Disaster Mitigation: The Case of Umbulharjo Merapi Monitoring Community on Merapi Mount, Indonesia - Nurjanah, Adhianty; Apriliani, Riski (Jurnal Hubungan Internasional, 2021)
Natural disasters are events that often occur in Southeast Asia, including in Indonesia. As it is situated in the ring of fire area and has faced different kinds of natural disaster events, Indonesia has their own experiences in disaster risk management, one of which is the involvement and active role of the community. Therefore, this study will analyze the important role of Umbulharjo Merapi Monitoring Community (UMMC)––a community that focuses on monitoring Mount Merapi in the Special Region of Yogyakarta––that is committed as the provider of information regarding Merapi condition through a direct monitor and plays the role in initiating programs that focus on disaster mitigation. The results of this study aims to show that the role of the community is necessarily required in the mitigation program so that it can be a reference for disaster management models in disaster-prone areas in the Southeast Asian region. This study used a qualitative descriptive method and the data were obtained through an in-depth interview process involving community members, academicians and the government of Sleman Regency. The results of the study revealed that the disaster mitigation carried out by UMMC consisted of four stages that are: identification, analysis, treating, monitoring and evaluation. Through these four stages, several programs for disaster risk reduction are arranged, such as counselling, training, collaborating with stakeholders, and mentoring.